Republic of Belarus : Staff Report for the 2003 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2003)
This 2003 Article IV Consultation states that Belarus made noticeable progress in some areas of economic reform over the past several years, but overall macroeconomic performance in 2002 was mixed. Inflation in 2002 was the lowest since Belarus became independent, yet it remains the highest in the Commonwealth of Independent States. Under current policies, the outlook for 2003 is broadly similar to the outcome for 2002. Inflation is expected at about 27 percent, and real GDP growth is likely to slow modestly to about 4 percent.